Study on the application of case based learning combined with mind mapping in anesthesia practice teaching using high-fidelity human patient simulation (以案例为基础的学习结合思维导图应用于高仿真模拟人麻醉实践教学的研究) - FAN Xiaoying (范晓英); XUE Sha (薛沙); LI Jing (李静); CHEN Zhengze (陈正泽); XU Xu (徐旭) (Journal of International Translational Medicine Limited, 2024)
Objective To explore the effect of case-based leaning (CBL) combined with mind mapping in anesthesia practice teaching using high-fidelity human patient simulation. Methods Totally 20 undergraduate interns of anesthesiology in grade 2018 were randomly divided into control group and observation group, with 10 students in each group. The control group adopted CBL combined with high-fidelity human patient simulation teaching mode, while the observation group adopted CBL combined with mind map in high-fidelity human patient simulation teaching mode. After the teaching, the teaching effects of the two groups were compared by examination, reaction time of complications and questionnaire. Results The theoretical basic scores and case analysis scores in the observation group were higher than those in the control group (92. 14±2. 81 vs. 89. 89±1. 32) and (92. 03 ± 2. 75 vs. 89. 23 ± 1. 42), with statistically significant differences (P<0. 05). The reaction time of complications in the observation group (8. 16±1. 42 minutes) was significantly shorter than that in the control group (16. 12±2. 75 minutes), with a statistically significant difference (P<0. 05). The observation group was 100. 00% satisfied with this teaching mode, 100. 00% of interns believed that it could increase autonomous learning ability, 90. 00% of interns believed that it could stimulate interns interest in learning and improve clinical practice ability, and 80. 00% of interns believed that it could cultivate clinical thinking ability. Compared with the control group, the above evaluation indexes were statistically significant (P<0. 05). Conclusion The teaching mode of CBL combined with mind map in anesthesia practice teaching using high-fidelity human patient simulation can help students independently summarize knowledge points, exercise clinical thinking, stimulate learning interest, and help improve learning efficiency and teaching quality. (目的 探讨以案例为基础的学习(CBL)结合思维导图应用于高仿真模拟人麻醉实践教学的效果。方法 选取2018级麻醉学本科实习生20人, 随机分为对照组和观察组, 每组10名。对照组采用CBL结合高仿真模拟人实践教学模式, 观察组采用CBL结合思维导图高仿真模拟人实践教学模式。教学结束后, 通过考核、处理并发症反应时间、调查问卷比较两组教学效果。结果 观察组理论基础成绩(92. 14±2. 81)分和病例分析成绩(92. 03±2. 75)分, 高于对照组理论基础成绩(89. 89±1. 32)分和病例分析成绩(89. 23±1. 42)分, 差异有统计学意义(P＜0. 05)。观察组处理并发症反应时间(8. 16±1. 42)min, 明显短于对照组(16. 12±2. 75)min, 差异有统计学意义(P＜0. 01)。观察组100. 00%(10/10)对此教学模式满意, 100. 00%(10/10)认为可以增加自主学习能力, 90. 00%(9/10)认为能激发学习兴趣和提升临床实践能力, 80. 00%(8/10)认为能培养临床思维能力, 与对照组比较, 上述各评价指标差异均有统计学意义(P＜0. 05)。结论 CBL结合思维导图在高仿真模拟人模拟操作的教学模式可以帮助学生自主归纳总结知识点, 锻炼临床思维, 激发学习兴趣, 有助于提高学习效率和教学质量。)